Determinants of Customer Satisfaction in Internet Mobile: Study on College Student - Rosa Lesmana; Hamdy Hady; Hari Muharam (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia, 2023)
This study aims to determine and analyze the impact of service quality, price and promotion on customer satisfaction of xl Axiata mobile internet among college students in South Tangerang. The type of research used is descriptive survey and explanatory research with verificative method. The population of the study was students from the three universities with a highest number of students in South Tangerang, the sample used the purposive sampling method by determining the sample size using the general reference of SEM sample, which is 5-10 times the number of indicators according to Hair in Supriyadi, 2014. The sample of 220 respondents. Data collected by questionnaires. The data analyzed with Sturctural Equation Modelling (SEM) and the tools using Lisrel 8.80. The result of the study revealed that service quality had a positive and significant effect on customer satisfaction, price had a positive and significant effect on customer satisfaction and promotion had a positive and significant effect on customer satisfaction, simultaneously service quality, price and promotion have a positive and significant effect on customer satisfaction.